An Audio-visual Approach to Teaching the Social Aspects of Sustainable Product Design - Watkins, Matthew Alan (FormAkademisk, 2015)
This paper considers the impact of audio-visual resources in enabling students to develop an understanding of the social aspects of sustainable product design. Building on literature concerning the learning preferences of ‘Net Generation’ learners, three audio-visual workshops were developed to introduce students to the wider social aspects of sustainability and encourage students to reflect upon the impact of their practice. The workshops were delivered in five universities in Britain and Ireland among undergraduate and postgraduate students. They were designed to encourage students to reflect upon carefully designed audio-visual materials in a group-based environment, seeking to foster the preferences of Net Generation learners through collaborative learning and learning through discovery. It also sought to address the perceived weaknesses of this generation of learners by encouraging critical reflection. The workshops proved to be popular with students and were successful in enabling them to grasp the complexity of the social aspects of sustainable design in a short span of time, as well as in encouraging personal responses and creative problem solving through an exploration of design thinking solutions.